Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Centurioni, Luca R.; Turton, Jon; Lumpkin, Rick; Braasch, Lancelot; Brassington, Gary; Chao, Yi; Charpentier, Etienne; Chen, Zhaohui; Corlett, Gary; Dohan, Kathleen; Donlon, Craig; Gallage, Champika; et al. (Frontiers in Marine Science, 2019)
The air-sea interface is a key gateway in the Earth system. It is where the atmosphere sets the ocean in motion, climate/weather relevant air-sea processes occur and pollutants (i.e., plastic, anthropogenic carbon dioxide, radioactive/chemical waste) enter the sea. Hence, accurate estimates and forecasts of physical and biogeochemical processes at this interface are critical for sustainable blue economy planning, growth and disaster mitigation. Such estimates and forecasts rely on accurate and integrated in-situ and satellite surface observations. High-impact uses of ocean-surface observations of Essential Ocean/Climate Variables (EOVs /ECVs) include 1) assimilation into/validation of weather, ocean and climate forecast models to improve their skill, impact and value; 2) ocean physics studies (i.e., heat, momentum, freshwater and biogeochemical air-sea fluxes) to further our understanding and parameterization of air-sea processes; and 3) calibration and validation of satellite ocean products (i.e., currents, temperature, salinity, sea level, ocean color, wind, waves). We review strengths and limitations, impacts, and sustainability of in-situ ocean surface observations of several ECVs and EOVs. We draw a 10-year vision of the global ocean-surface observing network for improved synergy and integration with other observing systems (e.g., satellites), modeling/forecast efforts and for a better ocean observing governance. The context is both the applications listed above and the guidelines of frameworks such as IOC-WMO-UNEP-ICSU GOOS, GCOS, and WIGOS. Networks of multiparametric platforms, such as the global drifter array, offer opportunities for new and improved in-situ observations. Advances in sensor technology (e.g., low-cost wave sensors), high throughput communications, evolving cyberinfrastructures and data information systems with potential to improve the scope, efficiency, integration and sustainability of the ocean surface observing system are explored.